Cycle Time Study in Improving Production Output in the Garment Industry Sewing Line - Kurnianingtias, Mayesti; Wibowo, Thiara Ananda; Khairunnisa, Hasna; Astrini, Galuh Yuli; Purwanningrum, Dinarisni (Teknik Industri Universitas Ma Chung, 2024)
The garment industry is one of the fastest-paced production environments, where speed and accuracy are crucial for meeting global customer demand. Cycle time plays an important role in satisfying the speed factor as it represents the overall time needed to produce a single piece of a product. Maintaining an appropriate cycle time is key to achieving production line balance. This study aims to analyze the cycle time of men's jacket production on a sewing line in an Indonesian garment industry by comparing the actual cycle time with the standard cycle time based on the operation breakdown for each production process step. Four significant discrepancies in actual cycle time were identified, ranging from 16% to 95%, indicating that the actual cycle time was significantly longer than the standard cycle time. The root cause of the highest cycle time was analyzed using Fishbone and 5 Whys analysis to understand the problem from each factor and sub-factor. Six improvement action plans were proposed and implemented, resulting in a 57.81% reduction in actual cycle time, from 127.66 seconds to 53.85 seconds, making it 17.66% faster than the standard cycle time. Furthermore, the total output per hour increased by approximately 216.67%, from 12 pieces to 38 pieces. This result implies that the study successfully identified the root of the problem on the sewing line and managed to increase production output.